DISCREPANCY BETWEEN PERCEIVED AND OBSERVED TEACHING CREATIVITY OF ENGLISH TEACHERS - Ketut Sujana; Luh Putu Artini; Ni Nyoman Padmadewi (Universitas Muhammadiyah Kalimantan Timur, 2021)
This study was aimed to investigate the discrepancy that occurred between the teachers’ perception and the observed implementation in teaching creativity in the classroom. Embedded mixed method QUAL (quan) was used as the design of the study. The data corpus comprises primary and supportive data, in which the first refers to qualitative data and the later were the supportive data. SMA Negeri 1 Melaya was selected as the research setting and two English teachers were selected as the research subject. The questionnaires and in-depth interview were used as the instrument to collect the data. The data from the questionnaires were analysed quantitatively and qualitatively. Then, data reduction was used to analyse the data from in-depth interview. The result demonstrates that the discrepancy occur between teachers’ perception and the observed implementation in the classroom. The teachers perceive themselves as creative, however the observational set data indicate that their teaching mostly focus on using conventional media, deductive learning, teacher centre technique, monotonous teaching activity, using same media in every meeting, rarely conducting innovative activity and integrating the contextual problem as learning material in the class. Their teaching also mainly focused on offline learning and printed media. In addition, they were also hardly found to show effort to redesign old media to be unique and creating attractive activities in the class.